2019
DOI: 10.1103/physrevapplied.12.044054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Classical Control Electronics on Qubit Fidelity

Abstract: Quantum processors rely on classical electronic controllers to manipulate and read out the quantum state. As the performance of the quantum processor improves, non-idealities in the classical controller can become the performance bottleneck for the whole quantum computer. To prevent such limitation, this paper presents a systematic study of the impact of the classical electrical signals on the qubit fidelity. All operations, i.e. single-qubit rotations, two-qubit gates and read-out, are considered, in the pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 74 publications
0
72
0
Order By: Relevance
“…Now that high fidelity control and readout of single-and two-qubit gates in semiconductor have been demonstrated, the next challenge lies in how to scale it to tens and hundreds of qubits. Corresponding constraints and problems were investigated thoroughly since 2015, including the geometry and operation time constraints [177,178], engineering configuration for quantum-classical interface [179][180][181][182], and even the quantifying of system extensibility [183]. In the light of these discussions, several proposals for scaling up were proposed, varying from the crossbar network [38,39] for spin-1/2 qubits in silicon MOS quantum dots, the two dimensional lattice of donor qubits in silicon [35,36], to the hybrid architecture like donor-dot structure [37] and flip-flop qubit structure [113].…”
Section: Scalable Designmentioning
confidence: 99%
“…Now that high fidelity control and readout of single-and two-qubit gates in semiconductor have been demonstrated, the next challenge lies in how to scale it to tens and hundreds of qubits. Corresponding constraints and problems were investigated thoroughly since 2015, including the geometry and operation time constraints [177,178], engineering configuration for quantum-classical interface [179][180][181][182], and even the quantifying of system extensibility [183]. In the light of these discussions, several proposals for scaling up were proposed, varying from the crossbar network [38,39] for spin-1/2 qubits in silicon MOS quantum dots, the two dimensional lattice of donor qubits in silicon [35,36], to the hybrid architecture like donor-dot structure [37] and flip-flop qubit structure [113].…”
Section: Scalable Designmentioning
confidence: 99%
“…In summary, the performance of the analyzed setup is sufficient to drive single-qubit operations in an ideal quantum processor with a 99.9% fidelity. More in general, it can be concluded that typically adopted general-purpose instruments are not limiting the fidelity of state-of-theart quantum computers, as shown in [60], since solid-state semiconductor qubits with fidelity exceeding 99.9% have been only recently demonstrated [73]. While this situation is desirable for current developments focused on improving the performance of quantum processors, the large performance margin in the electronic interface may not be tolerated as the performance and the scale of quantum processors improve, as discussed in Section 4.…”
Section: Controller Performance Versus Signal Requirementsmentioning
confidence: 95%
“…The effect of signal non-idealities can be either simulated [58] or analytically evaluated [59,60]. As an example, the sources of inaccuracy and the related specifications of the microwave pulse that achieves a 99.9% fidelity for a π-rotation on a single-electron spin qubit are shown in Table 2.…”
Section: Controller Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the energy efficiency of a cryogenic platform for the classical control of a scalable quantum computer is essential. Low power dissipation is required, down to few watts at 4K [24] to enable Fig. 5.…”
Section: Energy Efficiency Optimization Down To 43kmentioning
confidence: 99%